Arabic Language Competency For Prospective Non-Native Preachers - Hamdan, Iqbal; Asbulah, Lily Hanefarezan; Nazri, Omar; Kamaruzaman, Khairul Nazmi (Ijaz Arabi Journal of Arabic Learning, 2025)
Arabic is a cornerstone of Islamic da’wah, serving as the primary medium for understanding the sources of Islam, such as the Quran and Hadith. However, a gap in Arabic language competency among prospective non-native preachers raises concerns about how this deficiency impacts the effectiveness of their da’wah activities. This study aims to evaluate the Arabic language proficiency among prospective non-native preacher students and its relationship with the effectiveness of their da’wah efforts. A quantitative approach was employed using a questionnaire administered to 72 third-year students from the Dakwah and Leadership Studies program at Universiti Kebangsaan Malaysia. Data were analyzed using SPSS to assess Arabic proficiency levels and their correlation with da’wah effectiveness. The findings indicate that while Arabic proficiency levels are moderate, there is a significant and positive relationship between Arabic language competency and the effectiveness of da’wah. This study proposes proactive measures such as intensive training and integrating Arabic into da’wah activities to enhance the language competency of future preachers. The study also highlights avenues for further research into Arabic proficiency and its role in da’wah effectiveness.